PENGARUH KARAKTERISTIK DEWAN KOMISARIS TERHADAP PENGUNGKAPAN INTERNET FINANCIAL REPORTING (IFR) (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013) - M. Riduan Abdillah (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2015)
Abstract, This research aims to analyze the influence characteristic board of commissioners on the disclosure of Internet Financial Reporting (IFR). Characteristic board of commissioners in this research proxied by board size, independent board and board of commissioners activity. The population in this research is a manufacturing company that is listed on the Indonesia Stock Exchange (IDX) Year 2013. Based on purposive sampling method, the number of samples in the research of 102 companies. Testing the research hypotheses using multiple regression analysis by SMART PLS 2.0 M3. Results of hypothesis testing indicate that board size a significant positive effect on the disclosure of Internet Financial Reporting (IFR). Independent board and board of commissioners activity had no significant effect on the disclosure of Internet Financial Reporting (IFR).